Strategi Kepemimpinan Transformasional Berbasis Nilai Islam dalam Mencapai Keunggulan Lembaga Pendidikan Islam - Feri Rustandi; Isop Syafei (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This study aims to analyze and identify transformational leadership strategies based on Islamic values that effectively drive positive change and achieve excellence in Islamic educational institutions. By integrating Islamic values into the dimensions of transformational leadership, the findings reveal that these strategies enhance educational quality, shape students’ noble character, and strengthen institutional competitiveness. The findings also highlight the importance of continuous training, community collaboration, and the development of an inspiring vision as key steps in implementing these strategies. However, the study's limitations include a narrow data scope and insufficient exploration of the role of technology in supporting institutional transformation. This research provides significant contributions both theoretically and practically, offering concrete guidelines for leaders of Islamic educational institutions to create sustainable transformation. In conclusion, transformational leadership based on Islamic values is a relevant strategic approach to addressing global challenges and achieving the vision of excellence in Islamic education.